THE WORD SHIFT FOUND IN ARIPAN, SOLOK - Dian Dian; Saunir Saun (Universitas Negeri Padang, 2017)
This research is rooted in a number of language phenomena that occur in society. The phenomena can be categorized into word shifts. The word shift occurs because of age shifts, status differences and so forth. The contents of the word will be grouped into the type and cause of the word changes in this paper. The method used is descriptive research method. The data source of this research is the young generation and the older generation in Aripan, Solok. To obtain accurate data, the process was conducted by interviewing 10 informants consisting of 5 young people and 5 older generations. From the results of the discussion, the authors found 3 types of changes that occur in these words, namely lexical change (95), sound change (4), and lexical and semantic change (1). In addition, from the discussion also found 2 factors causing the change in the words, namely language contact and spelling pronunciation.